2016
DOI: 10.20471/acc.2016.55.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Vitamin D Level and Glaucoma in Women

Abstract: SUMMARY -Th e aim of the study was to determine whether serum vitamin D level is lower in female patients with glaucoma as compared with control group. Th e mechanism by which vitamin D reduces intraocular pressure is not fully clarifi ed. Almost all tissues possess vitamin D receptor (VDR). Th e mice lacking VDR (VDR knockout mice) have greatly contributed to the understanding of the general vitamin D physiologic function. VDR has been found in some ganglion layer cells, external and internal nuclear layers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…They found a vertically reversed J-shaped association of serum 25-hydroxyvitamin D with OAG (OR [95% CI]: 1.61 [1.09–2.38] for the lowest quintile compared to the second highest quintile; P-trend [quadratic] = 0.02), with a more pronounced effect in males [ 46 ]. Similarly, two other studies showed lower serum 25-hydroxyvitamin D levels in POAG patients [ 47 , 48 ]. In contrast, the retrospective cross-sectional Kangbuk Samsung health study did not find any difference in total vitamin D levels between patients with and without glaucoma [ 49 ].…”
Section: Resultssupporting
confidence: 53%
“…They found a vertically reversed J-shaped association of serum 25-hydroxyvitamin D with OAG (OR [95% CI]: 1.61 [1.09–2.38] for the lowest quintile compared to the second highest quintile; P-trend [quadratic] = 0.02), with a more pronounced effect in males [ 46 ]. Similarly, two other studies showed lower serum 25-hydroxyvitamin D levels in POAG patients [ 47 , 48 ]. In contrast, the retrospective cross-sectional Kangbuk Samsung health study did not find any difference in total vitamin D levels between patients with and without glaucoma [ 49 ].…”
Section: Resultssupporting
confidence: 53%
“…14 Therefore, vitamin D may influence the response of the optic nerve to damage under glaucomatous conditions. However, studies of the association of vitamin D levels with glaucoma are conflicting, with some [15][16][17][18] but not…”
Section: Introductionmentioning
confidence: 99%
“…In a crossover, randomized clinical trial involving 57 glaucoma patients, oral vitamin B 3 supplementation for 6 weeks at 1.5 g/day, then for 6 weeks at 3.0 g/day, improved RGC function, but without affecting the IOP and RNFL thickness [249]. Previous studies have reported that serum vitamin D levels are significantly lower in glaucoma patients as compared to healthy subjects [250,251]. Additionally, the presence of polymorphisms in vitamin D receptors, e.g., the BsmI 'B' allele and TaqI 't' allele, was shown to be a relevant risk factor in the development of POAG [251].…”
Section: Vitaminsmentioning
confidence: 95%